(untitled) (Research, Society and Development, 2025)
Basic sanitation is essential for public health, social well-being, and environmental preservation, but Brazil faces significant deficits in the sector. This article aims to analyze the contributions of the New Legal Framework for Basic Sanitation (SB) and the National Solid Waste Policy – PNRS to the advancement of sanitation in the country and to highlight the importance of these initiatives, their changes, and impacts on society. The New Framework establishes ambitious universalization goals, promotes the regionalization of services, requires bidding processes, and expands the powers of the National Water Agency (ANA), seeking to modernize the sector and attract private investment. The research, using a qualitative, exploratory, descriptive, and bibliographic approach, was used to achieve the research objective of analyzing the contributions of the new basic sanitation legal framework and the PNRS to the development of basic sanitation in Brazil and highlighting the importance of these initiatives, their changes, and impacts on society. Additionally, the PNRS strengthens integrated solid waste management, establishes reverse logistics, and determines the environmentally appropriate disposal of waste, contributing to sustainability and the circular economy. Both legislations make progress in overcoming historical sanitation challenges, although obstacles persist, especially in implementation in rural and peripheral areas. Thus, these policies are fundamental to promoting sustainable development, public health, and social inclusion in Brazil.